Limited Sequence Variation and Similar Phenotypic Characteristics of HIV-1 Subtype C Gag Variants Derived From the Reservoir and Pre-Therapy Plasma - Ojwach, Doty; Gounder, Kamini; Mulaudzi, Takalani; Gumede, Nombali; Baiyegunhi, Omolara O.; Reddy, Kavidha; Giandhari, Jennifer; Dong, Krista L.; Ndhlovu, Zaza; Ndung’u, Thumbi; Mann, Jaclyn K. (Frontiers in Virology, 2022)
HIV variants present in the reservoir, particularly in tissues, may differ from those present in peripheral blood prior to therapy initiation, and characterisation of these reservoir variants could better inform immune-based interventions for HIV cure. In the present study, Gag sequence differences between variants derived from the lymph node and peripheral blood mononuclear cell (PBMC) reservoirs as well as those derived from pre-therapy plasma, were investigated in 24 HIV-1 subtype C-infected individuals. HIV gag amplification was successful for 20 individuals, where 4 were controls including one untreated individual and 3 early treated individuals with LN collection within 2 weeks of treatment initiation. The remaining 16 individuals with LN and PBMC collection > 3 months after treatment initiation (median = 665 days), were further characterised. Recombinant viruses encoding patient-derived Gag-protease sequences from the pre-therapy plasma, LN reservoir, and PBMC reservoir, were constructed and the replication-competent viruses that grew in vitro were used to further investigate whether there are specific features of Gag reservoir variants that may have relevance for strategies to cure HIV. Virus characteristics measured included replication capacity, interferon-alpha resistance, cell-to-cell spread ability, and induction of antiviral cytokines. A limited number of novel Gag mutations (median = 4) in the reservoir of 3/7 early treated participants and 9/9 late treated participants were observed, where the majority of these mutations were likely cytotoxic T lymphocyte (CTL)-driven and 48% were represented in the replication-competent viruses. The reservoir variants had very few unique potential CTL escape mutations (median = 3) in Gag compared to the number of these Gag mutations that were already present in the plasma-derived virus (median = 23) at the time of treatment initiation, which was similar whether treatment was initiated late or early. The data suggest that the extent of CTL escape in Gag overall is likely similar between early and late treated individuals as well as between the reservoir and pre-therapy variants. The sequence differences in Gag that were unique to the reservoir viruses did not result in significantly altered virus characteristics overall, and are therefore unlikely to affect effectiveness of immune-based interventions for virus eradication.